Host monitoring of quorum sensing during Pseudomonas aeruginosa infection - Moura Alves, P; Puyskens, A; Stinn, A; Klemm, M; al., E (American Association for the Advancement of Science, 2019)
Pseudomonas aeruginosa rapidly adapts to altered conditions by quorum sensing (QS), a communication system that it uses to collectively modify its behavior through the production, release, and detection of signaling molecules. QS molecules can also be sensed by hosts, although the respective receptors and signaling pathways are poorly understood. We describe a pattern of regulation in the host by the aryl hydrocarbon receptor (AhR) that is critically dependent on qualitative and quantitative sensing of P. aeruginosa quorum. QS molecules bind to AhR and distinctly modulate its activity. This is mirrored upon infection with P. aeruginosa collected from diverse growth stages and with QS mutants. We propose that by spying on bacterial quorum, AhR acts as a major sensor of infection dynamics, capable of orchestrating host defense according to the status quo of infection.